Lean Green Tendency: a Systematic Literature Review - Silva, Cláudia Sousa e; Azevedo, Sara; Fonseca, Maria (Brazilian Journal of Operations & Production Management, 2024)
Lean philosophy and Green practices have been identified as management approaches that allow organizations to reach better economic and environmental results. Nevertheless, some authors argue that results can be enhanced with the integration of the Lean and Green practices. This synchronous effort has led to the developing a new Lean philosophy branch, the Lean Green. Goal: This work aims to deepen the Lean Green state of the art, as well as to understand how companies have adopted it. Design / Methodology / Approach: The methodology was supported by a systematic literature review following three steps: Planning, data collection, data analysis throughout content analysis. Results: The results showed that Lean Green is still an emerging theme in scientific research, with an increasing trend of publications worldwide in the last six years, adopting distinctive research strategies. Companies’ main motivations and barriers to adopting Lean Green were also identified. Finally, were identified the key factors that could help organizations to adopt Lean Green, namely critical implementation factors, facilitator models and tools, and the main results and advantages obtained. Limitations of the investigation: The main work´s limitation is that it was considered only the Scopus database. Practical implications: Help companies find solutions that enhance their performance and competitiveness, reduce their environmental impact, and improve their social responsibility. Originality/Value: The originality of this work is defended by crossing the results at the academic and practical levels. This allows the usefulness of academic research results by bringing them into a practical organizational context.